Secondary Slang Found on Song Lyrics; Drake’s World - Vinsensius Aleksandro Rivaldo Jegau; Ni Nyoman Deni Ariyaningsih (Universitas Islam Negeri Palopo, 2026)
Slang plays a crucial role in shaping linguistic style and cultural expression in contemporary music, particularly in hip-hop lyrics. Although numerous studies have examined slang in general, limited attention has been given to secondary slang in song lyrics and its contribution to meaning and stylistic expression, especially in Drake’s work. This study aims to address this gap by analyzing the use of secondary slang in Drake’s song “8am in Charlotte,” with a focus on how secondary slang constructs meaning and enriches the linguistic and cultural depth of the lyrics. Employing a qualitative descriptive method, the study identifies 27 slang expressions in the song, of which 5 are classified as secondary slang. The theoretical framework integrates (Kipfer & Chapman’s, 2007) classification of slang with (Claire, 1990) theory of meaning to interpret how secondary slang conveys contextual, social, and expressive meanings. The findings indicate that although secondary slang appears less frequently than other types of slang in the song, its presence is recurrent and functionally significant in conveying meaning and stylistic expression. This finding demonstrates that secondary slang functions as a strategic linguistic resource rather than merely informal language, contributing to the reinforcement of social identity and the enhancement of lyrical expression. In conclusion, this study contributes to a deeper understanding of the semantic and sociocultural functions of secondary slang in contemporary music and provides a valuable reference for future research in linguistics, popular culture, and music studies.